Does sports participation affect the mediating role of impulsivity in the association between adverse childhood experiences and aggression? - Janković, Marija; Van Boxtel, Geert; Bogaerts, Stefan (Frontiers in Psychology, 2024)
Adverse childhood experiences (ACEs) and self-reported aggression have often been associated, however, the mediating and moderating mechanisms underlying this association are not fully understood. In addition, less is known about potential factors that could serve as protection against the development of aggressive behavior. In this study, we investigated a moderated mediation model of sports participation and five impulsivity traits including positive and negative urgency, sensation seeking, and lack of premeditation and perseverance, in the association between ACEs and two forms of aggression. The final sample comprised 651 (68.5% females) individuals from a Dutch community ranging in age from 18 to 82 years (M = 34.08). Contrary to our expectations, sports participation did not affect the associations of ACEs, the five impulsivity traits, and reactive and proactive aggression, except the association between ACEs and lack of premeditation. Specifically, the detrimental effect of ACEs on the propensity to act without thinking, increases among individuals with lower levels of sports participation. In addition, it was also found that sports participation directly contributed to higher levels of sensation seeking. Finally, after controlling for sociodemographic variables, the positive association between ACEs and reactive aggression was significantly mediated by negative urgency, lack of perseverance, and lack of premeditation, while the positive association between ACEs and proactive aggression was significantly mediated by lack of premeditation and positive urgency. The findings of this study add to the body of knowledge about the role of sports participation and impulsivity traits in the development of both forms of aggression, however, replication studies among multiple populations are needed before firm conclusions can be drawn.